(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
In recent years, there has been a growing interest in spirituality, particularly among younger generations. Generation Z (Gen Z), typically defined as individuals born between 1997 and 2012, is the first cohort to have grown up with digital technology as an integral part of their daily lives. As this generation transitions into adulthood, their perceptions and attitudes toward spirituality appear to diverge from those of previous generations. The aim of this study is to examine the spiritual practices of Gen Z, focusing on the techniques employed, the frequency of engagement, and the factors influencing their practice. Additionally, the study seeks to explore gender differences in the perceived importance of spirituality and to investigate the relationship between belief in spirituality and mental well-being. A total of 100 respondents were selected through convenience sampling, and data were collected using a self-constructed questionnaire. The findings indicate that Gen Z increasingly utilizes practices such as meditation, mindfulness, and yoga as tools for managing stress, anxiety, and emotional well-being. Furthermore, the results suggest that females place greater importance on spirituality in their lives compared to males. A significant positive correlation was found between belief in spirituality and mental well-being, suggesting that a stronger belief in spirituality is associated with improved mental health among the respondents.